Modulators of receptor for advanced glycation end products signalling in the human endometrium. - Amy Katherine White (2011)
The immunoglobulin-like, transmembrane Advanced Glycation End product (AGE) Receptor (RAGE) is a pattern recognition receptor implicated in the transduction of pro-inflammatory signalling and processes. Over the past decade a substantial body of evidence has accrued implicating RAGE in the pathogenesis of several chronic inflammatory and vascular diseases such as diabetes, rheumatoid arthritis, amyloidosis, atherosclerosis and renal failure. More recently RAGE has been linked to cancer progression, possibly through its role in the inflammatory process. AGE products have been shown to exert their intracellular effects through ligation of their cognate receptor RAGE and the subsequent transactivation of NFKB signalling in several cellular contexts. Polycystic Ovary Syndrome (PCOS) is a reproductive endocrine disorder characterized by hyperandrogenism, chronic anovulation and insulin resistance, thus increasing the risk of diabetes mellitus in these patients. Non-enzymatically glycated AGEs are formed at an accelerated rate and accumulate in tissues in conditions of high glucose and oxidative stress. Interestingly, young normoglycemic women with PCOS exhibit higher serum AGE levels and increased RAGE expression in poly-cystic ovaries. RAGE is also regulated through the activity of the estrogen receptor (ER). The natural cyclical expression of estrogen throughout the menstrual cycle is perturbed in endometriosis even post menopause, suggesting that RAGE could also be dysregulated. Finally PCOS has been implicated in increased risk to endometrial cancer progression as has uterine exposure to the selective estrogen receptor modulator Tamoxifen (TX) therefore it is plausible that RAGE has a function in this disease. Objectives: The principal aims of this thesis were to characterise RAGE expression for the first time in fertile and infertile endometriotic and PCO human endometrium, and to initiate RAGE characterisation in endometrium obtained from patients with endometrial hyperplasia and cancer. Secondly, this thesis endeavoured to elucidate the transcriptional mechanisms regulating RAGE in vitro response to 17beta-estradiol and AGEs which are elevated in endometriosis and PCOS pathology respectively, and in endometrial cancer. Methodology: This project employed the use of real time Polymerase Chain Reaction (RT-PCR), Chromatin Immunoprecipitation (ChIP), Immunohistochemistry (IHC) and western blotting (WB). Results: Immunohistochemistry and RT-PCR data revealed that basal RAGE expression was significantly greater in PCO and endometriotic endometrium when compared to fertile controls, and significantly elevated in two cancer patients. RAGE was also characterised in endometrial cell models in which it was shown to be modulated at the mRNA and protein level by AGE-HSA, 17beta-estradiol (E2) and its antagonist 4-hydroxytamoxifen. Moreover, we have shown that RAGE is modulated by two distinct pathways through the estrogen receptor (ER) and NFKB. Novel ChIP results confirmed the presence of p65 and ER-alpha on the RAGE promoter at non- classical Spl and Apl sites in response to AGEs, E2 and TX. Conclusions: The results in this thesis may implicate endometrial RAGE expression in the infertility evident in women with PCOS and endometriosis. Furthermore, recent evidence implicates RAGE in mediating inflammation-driven tumourigenesis. Thus, over-expression of endometrial RAGE in PCOS and endometriosis, and in patients receiving tamoxifen for breast cancer treatment may predispose these women to an elevated risk of cancer.